18-6(x+3)=12(x-1)

Simple and best practice solution for 18-6(x+3)=12(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 18-6(x+3)=12(x-1) equation:



18-6(x+3)=12(x-1)
We move all terms to the left:
18-6(x+3)-(12(x-1))=0
We multiply parentheses
-6x-(12(x-1))-18+18=0
We calculate terms in parentheses: -(12(x-1)), so:
12(x-1)
We multiply parentheses
12x-12
Back to the equation:
-(12x-12)
We add all the numbers together, and all the variables
-6x-(12x-12)=0
We get rid of parentheses
-6x-12x+12=0
We add all the numbers together, and all the variables
-18x+12=0
We move all terms containing x to the left, all other terms to the right
-18x=-12
x=-12/-18
x=2/3

See similar equations:

| -3(4-5a)=30-6a | | 13x+21=34 | | 49=6m+7 | | 2(5x-3)-8=10+4x | | 4x+-5=7 | | 24x-2+70=180 | | 2/3(x+12)=22 | | 17+7j=67 | | 8x=720 | | 8x–200=144 | | 6x-2+116=180 | | B)(x+4)(x+2)-10=0 | | -z+9=11 | | –10+4k=10−k+10 | | -4x+7x+9=3(x+9) | | 6×(22+6)=w | | 6x-2=116 | | 4m+10+8m=–10+10m | | -1.2x-4+x=8+x-6 | | (3y+99)=(12y+9) | | -(4×+8)=2x-3(2x+3) | | 105x+105=180 | | y-1-0.6y=1.8 | | 3.8x=−19 | | 6=x*4+2 | | -3x-10+6x=-70+7x+16 | | 6=x+6*4 | | 6x-2x+14-2=104 | | 1.5x+2.5x=20 | | 18=30-4p | | 3x+2x+4=84 | | -31-4x=-5-5(1 |

Equations solver categories